Anaesthetic Considerations for Balloon Mitral Valvuloplasty in Pregnant Patient with Severe Mitral Stenosis: A Case Report and Review of Literature - Hemlata; Puneet Goyal; Satyendra Tewari; Arindam Chatterjee (Journal of Clinical and Diagnostic Research, 2017)
Even though, the incidence of Mitral Stenosis (MS) has reduced grossly, it still remains a health problem in developing countries and is the most common rheumatic valvular lesion encountered in pregnant patients. The already compromised cardiac status of a pregnant female deteriorates further by the presence of MS. So, pregnancy is a common situation during which untreated and frequently poorly tolerated MS are first diagnosed. Percutaneous Balloon Mitral Valvuloplasty (BMV) may be life saving in such a setting and a multidisciplinary approach in the management reduces the mortality and morbidity during the procedure. Anaesthetic management of such a procedure has hardly ever been reported. We report a case of a 23-year-old woman presenting at 28 weeks gestation with severe MS and severe pulmonary hypertension (52 mmHg) who underwent successful percutaneous BMV under monitored anaesthesia Care. The anaesthetic considerations in such situations are being discussed.